Aspek Perkembangan Peserta Didik Selama Masa Sekolah Dasar (6-12 Tahun) - Hemi Wulandari; Indah Adhani; Putri Chairany Hasibuan; Nur Andini; M. Khairil Fadli; Sri Wahyuni (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
This study aims to describe how students develop during the elementary school period (6-12 years) in Indonesia. This research is descriptive research with a qualitative approach. The data collection method is a literature study obtained from several sources such as books, journals and research articles that are appropriate to this research. The research results show that the characteristics of a child's development are different, and it depends on the factors that influence a person's development. The developmental characteristics of school-aged children include physical, motoric, intellectual, language development, social & emotional development, religious moral awareness. There are many factors that influence development which will cause problems in development. These factors include genetic factors and environmental factors. In this case, teachers must have knowledge in maximizing aspects of children's development. Apart from that, teachers must be able to foster good cooperation with parents, the community and all people involved in the smooth running of the education process at school.